The Crop Coefficient of Barley (Hordium vulgare) Under Gezira Conditions - Mohamed, Mahasin A.; Khair, Mohammed A. M.; Adam, Hussein S. (University of Khartoum Journal of Agricultural Sciences, 2023)
The development of regionally based and growth-stage-specific crop coefficient Kc helps in estimation of the crop water requirements (CWR) and irrigation planning. In this regard the Kc of barley is needed for the estimation of CWR in the Gezira and similar regions in the Sudan. An experiment was conducted for three consecutive seasons 2003/04, 2004/05 and 2005/06, at Gezira Research Station to determine the Kc of barley. The crop evapotranspiration (ETc), reference crop evapotranspiration (ET0 ) and the crop coefficient values as ratios of ETc to ET0 were calculated. The results showed that the Kc values of 0.48, 0.96, 1.04 and 0.48 were appropriate for the initial stage, crop development, and mid-season and late season stages, respectively. These Kc values could be used for estimation of CWR as a product of Kc * ET0 in the Gezira as well as other similar regions of the Sudan.